Learning Red Hat Linux, 3rd Edition - McCarty, Bill (O'Reilly, 2011)
The third edition of Learning Red Hat Linux guides you through the process of installing and running Red Hat Linux on your PC. Written in a friendly, easy-to-understand style, this book contains all you need to get started . With new tutorials covering OpenOffice Tools and the desktop, this book is excellent for first-time Linux users who want to install the operating system on a new PC or convert an existing system to Linux.